Trichuris trichiura infection is associated with changes in gut microbiome composition and function among women of reproductive age from Pemba, Tanzania - Nguélé, Aristide Toussaint; Mozzicafreddo, Matteo; Chen, Hongliang; Piersanti, Angela; Salum, Salum Seif; Ali, Said M.; Zhang, Junjie; Miceli, Cristina (Frontiers in Tropical Diseases, 2024)
Large intestine-dwelling helminths affect microbiome composition. In sub-Saharan Africa, where helminth infections are endemic, the use of chemotherapeutic drugs is the primary strategy for controlling soil-transmitted helminthiases (STHs). However, the emergence of anthelmintic resistance necessitates the urgent exploration of alternative and complementary treatments to achieve the World Health Organization’s goal of eliminating STHs. One promising avenue involves the manipulation of gut microbiota in at-risk populations. This study aimed to enhance the understanding of the interplay between Trichuris trichiura and the gut microbiome. In this study, we used the Mini-FLOTAC technique for parasitological analyses and a shotgun metagenomic sequencing approach to investigate the effect of T. trichiura on the gut microbiome by comparing infected and non-infected women of reproductive age (WRA) from Pemba. Structural and functional analyses of the gut microbiome revealed that T. trichiura infection shaped the host gut microbiome in WRA. Some taxa vary according to infection status. Prevotella genus was more abundant in healthy participants, whereas species such as Weissella cibaria, Leuconostoc citreum (new emergent probiotics), and Leuconostoc lactis (starter) decreased in infected individuals, suggesting the use of potential probiotic treatments to mitigate dysbiosis induced by STHs. Furthermore, the overall number of common fungi, irrespective of species, was significantly higher in the mycobiome of Trichuris infected participants. Functional analysis revealed significant differences in metabolic pathways (p < 0.05), with cholesterol metabolism and pathogenic infections being more abundant in the infected samples than in the non-infected samples. In conclusion, this study sheds light on the intricate interactions between helminth infections and the gut microbiome in the WRA, particularly in STH-endemic regions. The identified associations between specific gut microbial changes and T. trichiura infection may pave the way for innovative complementary treatments to effectively combat STHs.